A case of tick-transmitted Q fever in Lishui, China diagnosed by next-generation sequencing. Issue 9 (September 2021) - Huang, Jinwei; Wang, Rui; Gao, Can; Lü, Yuankai; Cao, Zhuo; Deng, Shanshan; Yue, Changwu
Q fever is a zoonotic disease caused by Coxiella burnetii . Most patients have non-specific symptoms at onset. In addition, routine diagnostic tests for C. burnetii are not sensitive, and the bacterium cannot grow in general culture medium. The diagnosis of Q fever therefore poses a challenge. This case study describes a man with a clear history of tick bite who had recurrent fever, pneumonia, and liver damage. Routine tests and bacterial cultures failed to clarify the pathogeny, but laboratory and imaging data suggested infection. After routine tests were exhausted, we detected the presence of C. burnetii in a whole blood sample using next-generation sequencing (NGS). To our knowledge, this is the first report of Q fever associated with Coxiella burnetii detected directly from blood samples in Lishui, China. NGS has revolutionized the diagnosis of infectious diseases, especially those caused by rare or newly discovered pathogens, and patient responses have finally proved its substantial benefits. NGS has important clinical significance for the early diagnosis of chronic Q fever. This proof-of-concept study is worthy of promotion in clinical practice.